The Technical Course in Cooperatives by PRONERA: an analysis based on the People’s Capabilities Approach - Conceição Coutinho Melo; Paulo Dabdab Waquil (Revista Brasileira de Educação do Campo, 2018)
This paper presents results from a research about the Cooperatives Thechnical Course (TAC), originated in the 90’s after a need of the MST for forming technical staff for working in cooperatives located in rural settlements as part of the Land Reform. Nowadays, the course is taught through the National Program of Education within the Land Reform (PRONERA), under the paradigm of Rural Education. Rural Education is understood as one of the motivations for the rural development, from a multidimensional viewpoint. Therefore, a challenging dialogue between Economy and Rural Education emerged, and contributed to a field little explored under the aegis of the People’s Capabilities Approach. In such approach, developed by the Indian Amartya Sen, development is seen as people’s capabilities expansion for living the lives they yearn, where monetary income is not essential for the well-being, but other variables (education, health, political liberty, etc.). The goal in this research was to investigate if the TAC contributes to the expansion of capabilities of its graduates and to the development of rural settlements. All the people interviewed graduated, and after that, worked in entities related to rural settlements. The TAC has contributed to the graduates’ liberty expansion.